Can the assignment of a financial claim be regarded as a financial instrument? - Andersons, Toms (Riga Graduate School of Law, 2018)
The main aim of this thesis is to provide with an answer to the question as to whether the assignment of financial claims should be regarded as constituting financial instruments. The question is interpreted from the perspective of the civil law legal system of Latvia, which is a part of the European Union (EU), the Eurozone, and also the common capital market of the EU. Therefore, the legislative acts of the EU relating to the subject matter are interpreted and analysed in conjunction with the substantive national law. Since the examined definition for the concept of assignment of claims has commonalites in other parts of the EU that share similar legal traditions the findings of this thesis may therefore be relevant to the potential analysis also in other countries.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Financial law